One Slope Model: Efforts to Optimize Wifi Networks in the Office of communication and informatics in Palembang - Winda Wulandari; Ari Muzakir (Journal of Information System and Informatics, 2020)
Information technology in the field of transmission that is currently developing, one of which is Wi-Fi. Wi-Fi devices provide user convenience in carrying out their activities. The quality of Wi-Fi network performance can be known by the reception of the signal received by the user. If the placement of an access point (AP) is done correctly, the network will be optimized. There are several propagation models in the room that can be used as a guideline in determining the placement of the AP, one slope model is a way to measure the average level of a building and only depends on the distance of the transmitter and receiver. This research was conducted in order to overcome the problem of Wi-Fi network area coverage at the Office of Communication and Information of the City of Palembang. This study conducted an experiment to change the layout of AP's placement, measure and calculate data in priority with the one slope model. The results of measurements and calculations carried out analysis and comparison in order to determine the results of the experiments conducted. The results of this study indicate that an attempt to change the AP layout with one slope model can overcome existing problems and get better Wi-Fi coverage area performance. In the calculation with the one slope model of the 2-trial access point placement results in a decrease and an increase in signal. The signal reduction occurred in experiment 1, whereas in experiment 2 (design 2) the signal increased by 1.46dBm.